Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1523/jneurosci.0710-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Heterogeneous Reactivity of the Syntaxin Molecules on the Inner Leaflet of the Plasma Membrane

Abstract: The soluble N-ethylmaleimide-sensitive fusion (NSF) attachment protein (SNAP) receptor (SNARE) protein syntaxin 1A forms nanosized clusters (membrane rafts) on the plasma membrane (PM) that are in equilibrium with freely diffusing syntaxin molecules. SNAREcomplex formation between syntaxin 1A and SNAP-25 (synaptosome-associated protein of 25 kDa) on the PM and synaptobrevin 2 on the vesicles (trans-SNAREs) is crucial for vesicle priming and fusion. This process might be impeded by the spontaneous accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…5). The results presented herein together with the model presented in Bar-On et al (20) for the kinetics of cis-SNARE complex formation might explain how syntaxin reactivity is affected by its position within and around clusters. The model suggests partitioning of the syntaxin molecules into three reactive states, depending on their environment.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…5). The results presented herein together with the model presented in Bar-On et al (20) for the kinetics of cis-SNARE complex formation might explain how syntaxin reactivity is affected by its position within and around clusters. The model suggests partitioning of the syntaxin molecules into three reactive states, depending on their environment.…”
Section: Resultssupporting
confidence: 63%
“…Accordingly, the densely packed molecules at the cluster center, being inaccessible to the external surroundings, are less reactive than the single syntaxin molecules that can interact freely with their partners. Moreover, the model indicates the presence of a fraction of clustered molecules that are semi-reactive and can interact with syntaxin partners, albeit with much slower kinetics (20). This fraction was suggested to represent molecules situated in the outer parts of the clusters, which are therefore more accessible to the surroundings than molecules in the center.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies using super-resolution imaging showed that syntaxin and SNAP25 form separate clusters with very little overlap, although they require each other for fusion (11)(12)(13). The clusters of syntaxin and SNAP25 are at equilibrium with free SNARE molecules, which are much more mobile (13,14). These free molecules occasionally form syntaxin-SNAP25 dimers termed "acceptor complex," which can interact with synaptobrevin during the fusion process (Ref.…”
mentioning
confidence: 99%